2014
DOI: 10.1007/s10143-014-0578-y
|View full text |Cite
|
Sign up to set email alerts
|

Resection of supratentorial gliomas: the need to merge microsurgical technical cornerstones with modern functional mapping concepts. An overview

Abstract: Although surgery is not curative for the majority of intracranial gliomas, radical resection has been demonstrated to influence survival and delay tumor progression. Because gliomas are very frequently located in eloquent or more generally critical areas, surgeons must always balance the maximizing resection with the need to preserve neurological function. In this overview, we tried to summarize the recent literature and our personal experience about (1) the benefits and limits of using preoperative anatomical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…WMT is the only preoperative noninvasive tool for studying white matter tracts, which is advantageous for risk stratification, patient counseling, and surgical planning (Berman, 2009, Farshidfar et al, 2014, Romano et al, 2009, Rosenstock et al, 2017). Understanding the spatial configuration of the white matter helps finding the safest corridor particularly in deeply situated lesions (Farshidfar et al, 2014, Spena et al, 2015, Tunc et al, 2015). For instance, Barbosa et al reported a statistically significant improvement of the post-operative Karnofsky Performance Scale by the implementation of WMT during the resection of insular gliomas (Barbosa et al, 2016).…”
Section: Supratentorial Lesionsmentioning
confidence: 99%
“…WMT is the only preoperative noninvasive tool for studying white matter tracts, which is advantageous for risk stratification, patient counseling, and surgical planning (Berman, 2009, Farshidfar et al, 2014, Romano et al, 2009, Rosenstock et al, 2017). Understanding the spatial configuration of the white matter helps finding the safest corridor particularly in deeply situated lesions (Farshidfar et al, 2014, Spena et al, 2015, Tunc et al, 2015). For instance, Barbosa et al reported a statistically significant improvement of the post-operative Karnofsky Performance Scale by the implementation of WMT during the resection of insular gliomas (Barbosa et al, 2016).…”
Section: Supratentorial Lesionsmentioning
confidence: 99%
“…Preoperative planning includes creating a precise threedimensional (3D) concept of the surgical target area and the trajectory leading to it. This is achieved by the acquisition and study of detailed multimodality imaging series, including CT, MRI, f-MRI, diffusion tensor imaging-tractography, and detailed arterial and venous vascular imaging [2,18,21,22,48,63,69]. According to preoperative imaging, the direction of aneurysm and the compensation of collateral circulation are closely related to the choice of surgical approach.…”
Section: Preoperative Imaging For Keyhole Surgerymentioning
confidence: 99%
“…In recent years, advances in brain imaging such as fibre tracking by diffusion imaging and functional mapping have shown their potential in the radiosurgical and surgical management of brain tumours [ 25 , 26 , 27 ]. These advancements could be beneficial should they be employed in the management of head and neck cancer treatment by monitoring brain microstructural changes.…”
Section: Introductionmentioning
confidence: 99%